Deletion analysis and clinical correlations in patients with Xp21 linked muscular dystrophy - Ülgenalp, Ayfer; Giray, Özlem; Bora, Elçin; Hızlı, Tülin; Kurul, Semra; Sağın-Saylam, Gül; Karasoy, Hatice; Uran, Nedret; Dizdarer, Gülşen; Tütüncüoğlu, Sarenur; Dirik, Eray; Özkınay, Ferda; et al. (The Turkish Journal of Pediatrics, 2004)
We carried out molecular deletion analysis on 142 patients with Duchenne/Becker muscular dystrophy which covered 25 exons of the dystrophin gene. We also evaluated the results by comparing with the clinical findings and examples in the literature. A deletion ratio of 63.7% was achieved. Exon 46 was the most frequently affected region. Interestingly we also observed four cases with muscle promoter (Mp) region deletions which have been rarely reported in the literature.